Krishi Vigyan Kendras and Agripreneurship: A Review on Entrepreneurial Development - Paul, Dr. Saima; Rayeess-Ul-Islam, Dr. Malik; Gani, Dr. Gazanfer (International Journal of Psychosocial Rehabilitation, 2021)
KVKs are centres for delivering agricultural knowledge, technology, and skill development to improve farm functioning. As institutions set up to curb sustainable agrarian practices and rural business, KVKs are central to making farmers into agripreneurs. This review intends to evaluate Krishi Vigyan Kendras, which have contributed significantly as centres for promoting agripreneurship, especially their entrepreneurial development programmes. By analysing the programmes, success stories, and challenges of KVKs in promoting agri-business ventures, this review will explain how KVKs assist farm producers in moving away from subsistence farming and becoming successful agripreneurs. From the literature, it is clear that KVKs play the centre stage in the development of agripreneurship through the generation and transfer of knowledge and the development of social capital. Furthermore, the focus should be on identifying and meeting the needs peculiar to women involved in agripreneurship with consideration for improving the efficiency of the KVKs that play a role in rural development. Further research should enhance the link between ED and the current techno-social structures of KVKs towards the effective promotion of agripreneurship. This will guarantee that knowledge-based verticals like the KVKs become a storehouse of all the information the rural area needs and a spring of sustainable rural enterprise.